ANALISIS GAYA TARI GANDAI SILAUT PESISIR SELATAN - Naurah Rania Husni; Nerosti (Universitas Negeri Padang, 2026)
This study aims to describe and analyze the dance style of Gandai Dance in Silaut District, Pesisir Selatan Regency. The research employs a qualitative approach with a descriptive method. Data was collected through observation, interviews, literature study, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data collection, data reduction, and data presentation. The results show that Gandai Dance has a performance structure consisting of opening, core, and closing sections, with six main movement variations forming structured movement motifs. The dance style is characterized by simple, rhythmic, and communicative movements with an emphasis on interaction between dancers, reflecting values of togetherness and politeness. In terms of movement dimensions, the dance utilizes one-, two-, and three-dimensional space, indicating varying levels of movement complexity. The elements of action and effort demonstrate a combination of light and strong energy, creating balanced movement dynamics. Supporting elements such as costume, floor patterns, and musical accompaniment including edab, sunai, and bapambak vocals further strengthen the character and identity of the dance. Overall, Gandai Dance functions not only as entertainment but also as a medium for preserving cultural values within the community.